The Effects of Child Care Teacher's Job Stress and Personality on Child Abuse Protective Behaviors - 김민곤; 허문영; 박상혁 (International Journal of Advanced Culture Technology(IJACT), 2024)
This study aims to examine the effects of child care teachers' job stress and personality on child abuse protective behaviors, which consist of perception and reporting intention of child abuse, and to verify the moderating effect of past child abuse experience. A survey was conducted on 246 child care teachers nationwide, and the collected data were analyzed through regression analysis and t-test. The results showed that job stress had a negative effect and personality had a positive effect on child abuse protective behaviors. In addition, there was a significant difference in the influence of job stress and personality on protective behaviors according to the presence or absence of past child abuse experience. Based on these results, practical implications for preventing child abuse by child care teachers were discussed.